Analysis Influence Compensation Financial and Non- Financial Compensation To Performance Employee With Satisfaction Work As Variables Moderation : Study On Employee Kpp Primary School in Malang City - Ahmad Matoyani Yarfak; Muryati Muryati; Survival Survival (Brilliant International Journal Of Management And Tourism, 2025)
This study aims to analyze the effect of financial compensation and non-financial compensation on employee performance with job satisfaction as a moderating variable . The approach in this study is a quantitative approach. This research strategy uses an associative strategy, which is based on the characteristics of the main research problem. The population of the study was all employees of KPP Pratama in Malang City, consisting of KPP Pratama Malang Utara and KPP Pratama Malang Selatan with a total of 154 employees. Determination of the number of samples used the Slovin formula of 61 employees. The sampling technique used in this study was proportionate stratified random sampling. The structural equation modeling of the study used Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS version 4.0 to analyze the data . The results showed that better financial compensation was able to encourage increased employee performance. Better non-financial compensation was able to encourage increased employee performance. Although job satisfaction was getting stronger, it was not able to encourage increased employee performance. Job Satisfaction is able to play a role in purely moderating the influence of Financial Compensation on Employee Performance. Job Satisfaction is able to play a role in purely moderating the influence of Non-Financial Compensation on Employee Performance.